Emerging Picture of Deuterosome-Dependent Centriole Amplification in MCCs - Umama Shahid (Cells, 2018)
Multiciliated cells (MCCs) have several hair-like structures called cilia, which are required to propel substances on their surface. A cilium is organized from a basal body which resembles a hollow microtubule structure called a centriole. In terminally differentiated MCCs, hundreds of new basal bodies/centrioles are formed via two parallel pathways: the centriole- and deuterosome-dependent pathways. The deuterosome-dependent pathway is also referred to as “de novo” because unlike the centriole-dependent pathway which requires pre-existing centrioles, in the de novo pathway multiple new centrioles are organized around non-microtubule structures called deuterosomes. In the last five years, some deuterosome-specific markers have been identified and concurrent advancements in the super-resolution techniques have significantly contributed to gaining insights about the major stages of centriole amplification during ciliogenesis. Altogether, a new picture is emerging which also challenges the previous notion that deuterosome pathway is de novo. This review is primarily focused on studies that have contributed towards the better understanding of deuterosome-dependent centriole amplification and presents a developing model about the major stages identified during this process.